Rejection sensitivity and multiple group memberships: The moderating role of an oxytocin receptor gene polymorphism. (4th May 2018) - Woods, Robbie; Bedard, Marc; McQuaid, Robyn Jane; Matheson, Kim; Anisman, Hymie
ABSTRACT: Rejection sensitivity is a cognitive-affective processing disposition that has been linked to interpersonal difficulties. In this regard, the neuropeptide hormone, oxytocin, is thought to underlie social cognitions and behaviors that promote social affiliation. A single nucleotide polymorphism (SNP) on the oxytocin receptor gene (OXTR), in which guanine (G) is substituted for adenine (A), has been associated with less support-seeking behaviors. In the current study, among 376 undergraduate students, it was shown that the relationship between rejection sensitivity and depressive symptoms was mediated by multiple group memberships. Furthermore, the relation between rejection sensitivity and group memberships was only evident among individuals possessing the A allele on the OXTR gene. These findings further support the psychosocial deficits characteristic of individuals possessing the OXTR polymorphism, which in turn is linked to poor mood.